2020
DOI: 10.1002/eat.23291
|View full text |Cite
|
Sign up to set email alerts
|

Gastric interoception and gastric myoelectrical activity in bulimia nervosa and binge‐eating disorder

Abstract: Objective Identifying factors that control food intake is crucial to the understanding and treatment of eating disorders characterized by binge eating. In healthy individuals, stomach distension plays an important role in the development of satiation, but gastric sensations might be overridden in binge eating. The present study investigated the perception of gastric signals (i.e., gastric interoception) and gastric motility in patients experiencing binge‐eating episodes, that is, bulimia nervosa (BN) and binge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 43 publications
2
19
1
Order By: Relevance
“…Few old studies suggest a role for gastric motility alterations in the development and/or maintenance of BN. Recently, Van Dyck et al reported a delayed response to satiation and abnormal gastric myoelectrical activity measured by electrogastrography before and after ingestion of noncaloric water, in 29 patients with BN and binge eating disorders vs controls ( 29 ). Moreover, patients with BN exhibit larger gastric capacities ( 30 ), reduced sensitivity to gastric distention ( 31 ), delayed gastric emptying ( 32 ), decreased post-prandial cholecystokinin (CCK) ( 32 ), and reduced gastric relaxation reflex ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Few old studies suggest a role for gastric motility alterations in the development and/or maintenance of BN. Recently, Van Dyck et al reported a delayed response to satiation and abnormal gastric myoelectrical activity measured by electrogastrography before and after ingestion of noncaloric water, in 29 patients with BN and binge eating disorders vs controls ( 29 ). Moreover, patients with BN exhibit larger gastric capacities ( 30 ), reduced sensitivity to gastric distention ( 31 ), delayed gastric emptying ( 32 ), decreased post-prandial cholecystokinin (CCK) ( 32 ), and reduced gastric relaxation reflex ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interoceptive accuracy (IAcc) assesses the participant’s ability to accurately perceive inner bodily sensations. Although measures of interoceptive accuracy have recently been piloted in different modalities [ 49 , 50 ], cardiac interoceptive accuracy measured by heartbeat counting [ 18 ] has been by far the most commonly used measure of interoceptive accuracy in the literature on: the role of interoception in emotional intensity [ 51 ]; emotion regulation [ 52 ]; cortical signatures of interoception [ 53 , 54 ]; and the degree of activation of cortical areas connected to the interoceptive matrix [ 55 ]. Interestingly, low IAcc (measured by heartbeat counting) has been linked to a variety of mental disorders [ 11 ] and also to CP conditions [ 9 , 20 ].…”
Section: Materials and Methods Studymentioning
confidence: 99%
“…Previous studies have found that accelerated false cardiac feedback (that is, exaggerated cardiac interoception) can modulate salience detection for an emotional picture (Gray et al, 2007) and perceived physical effort (Iodice et al, 2019). Also, an altered gastric interoception has been observed in people with an eating disorder compared with healthy controls (Van Dyck et al, 2021). Based on the functional difference in cardiac interoception and gastric interoception, we speculated that they would have distinct neural representation; specifically, cardiac interoception and gastric interoception may be encoded in the .…”
Section: Introductionmentioning
confidence: 93%